2023
DOI: 10.1111/jcpp.13753
|View full text |Cite
|
Sign up to set email alerts
|

Research Review: A systematic review and meta‐analysis of infant and toddler temperament as predictors of childhood attention‐deficit/hyperactivity disorder

Abstract: Background: Attention-deficit/hyperactivity disorder (ADHD) is a common neurodevelopmental disorder with onset as early as preschool and impairment across the lifespan. Temperament factors, specifically those that theoretically map onto ADHD symptoms, may be early markers of risk for developing later childhood ADHD that could be identifiable in infancy or toddlerhood. This meta-analysis examined the associations between these early temperamental factors and later symptoms and diagnosis of ADHD and mapped early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 89 publications
1
2
1
Order By: Relevance
“…While our study only found modest associations between activity level and ADHD traits across siblings, previous research indicate that activity level plays an important role in the development of ADHD (Kostyrka-Allchorne et al, 2020;Nigg, 2006). A recent meta-analysis found that higher activity levels in infants and toddlers predicted later ADHD traits and diagnosis, even after controlling for other aspects of temperament such as negative emotionality and effortful control (Joseph et al, 2023). Our findings align with recent research demonstrating a consistent predictive relationship between high activity level in infants and later ADHD.…”
Section: Strengths Limitations and Future Directionscontrasting
confidence: 87%
“…While our study only found modest associations between activity level and ADHD traits across siblings, previous research indicate that activity level plays an important role in the development of ADHD (Kostyrka-Allchorne et al, 2020;Nigg, 2006). A recent meta-analysis found that higher activity levels in infants and toddlers predicted later ADHD traits and diagnosis, even after controlling for other aspects of temperament such as negative emotionality and effortful control (Joseph et al, 2023). Our findings align with recent research demonstrating a consistent predictive relationship between high activity level in infants and later ADHD.…”
Section: Strengths Limitations and Future Directionscontrasting
confidence: 87%
“…Monitoring is the key word: while individual preschool time-points, starting at age 1.5 years for HI and 4 years for IN, predict the high trajectory outcomes, regression models show that each subsequent time-point adds to the prediction. These results are also consistent with studies showing that HI in toddlers, and possibly earlier, is more predictive as a dimension of ADHD than IN (Joseph et al, 2023). Overall, the phenotypic results suggest that timely monitoring is needed to assess risk more reliably than single screening assessments and that parents of preschoolers provide valuable information in that respect.…”
Section: Predicting Developmental Trajectoriessupporting
confidence: 87%
“…This emphasizes the combination between biology and environment: an individual's temperament is genetically influenced and thus relatively stable; however, it is still shaped by the environment individuals develop in and interact with over time. Infant temperament has been positively associated with later social competence (10), identified as a risk factor in the development of future psychopathology including ADHD (11) and externalizing/ internalizing behavioral problems (e.g., anxiety, depression) (12), and is often considered the building blocks of adult personality (13). Given this understanding of how temperament originates and its impact on long term development, it is not surprising the connection among temperament, fetal programming, and antenatal depression is being increasingly explored.…”
Section: Introductionmentioning
confidence: 99%